Cathode of proton battery and manufacturing method thereof
The use of Prussian blue analogues in proton batteries addresses the limitations of lithium-ion batteries by providing fast charging and long-lasting proton batteries with improved efficiency and sustainability.
Patent Information
- Application Number
- CN202380084300.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-07
- Filing Date
- 2023-12-07
- Publication Date
- 2025-07-15
AI Technical Summary
Existing lithium-ion batteries have problems such as short life, high cost, unrecyclable, poor safety, and inability to charge and discharge at low temperatures, and traditional battery technology is difficult to meet the needs of fast charging and long life.
Prussian blue analogue (PBA) coated on the current collector is used as the cathode material for the proton battery, combining cell-grade carbon nanoparticles and water-insoluble binder to form a proton battery structure with high capacity, fast charging and long life.
It achieves ultrafast charging rate, long life cycle, high safety, low cost and recyclable proton battery performance, with an overall efficiency of 97%, suitable for a variety of application scenarios.
Smart Images

Figure CN120322871A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology and methods of manufacturing batteries.
[0002] In one form, the present invention relates to a cathode for a proton battery and a method of manufacturing the same.
[0003] The cathode of the present invention related to copper and manganese Prussian blue analogues will be conveniently described hereinafter. However, it should be understood that the present invention is not limited to those types and can extend to a wider range of Prussian blue analogues. Background Art
[0004] It should be understood that any discussion of documents, devices, actions or knowledge in this specification is for the purpose of explaining the context of the present invention. In addition, the discussions throughout this specification are based on the inventors' knowledge and / or the inventors' perception of certain related technical problems. In addition, any discussion of materials (such as documents, devices, actions or knowledge) in this specification is for the purpose of explaining the context of the present invention based on the inventors' knowledge and experience. Therefore, any such discussion should not be regarded as an admission that any material constituted part of the prior art base or common general knowledge in the relevant field in Australia or elsewhere on the date of priority of the present disclosure and claims.
[0005] Lithium-ion batteries are widely used and are one of the most popular types of rechargeable batteries. Compared with traditional battery technologies, lithium-ion batteries charge faster, have a longer battery life, a high power density, and a longer battery life. Lithium-ion batteries have been mass-produced commercially and have good specific density and energy density.
[0006] However, lithium-ion batteries have several disadvantages. The typical life cycle of a lithium-ion battery is about 3 to 5 years or 500 to 1,000 charge cycles, charging at a low charging rate (usually 0.5C to 1C), which means that the average charging time is at least 1 to 3 hours. Lithium and other metals (including cobalt and nickel) used in lithium-ion batteries are becoming increasingly expensive. In addition, most components of lithium-ion batteries are almost non-recyclable; there are safety issues and sometimes they catch fire spontaneously.
[0007] Many considerations have driven the research on new battery chemistries to address the disadvantages of lithium-ion technology. These factors include the rising prices of lithium, cobalt and nickel, as well as the increasing emphasis on safety, environmental and technical issues. Several new battery chemistries have been proposed, including sodium-ion batteries, vanadium redox flow batteries, zinc bromide batteries, iron-air batteries and sodium-sulfur batteries.
[0008] Proton batteries are one of the latest additions to this evolving battery technology. Proton batteries are reversible proton exchange (PEM) fuel cells with integrated energy storage. The integration of these components (i.e., electrolyzers, storage, and fuel cells) is carried out at the nanoscale.
[0009] Proton batteries do not convert the generated protons (H + ) into molecular hydrogen (H2). Instead, the protons act as active energy carriers. This avoids the inefficiencies inherent in the conversion and reconversion of protons to molecular hydrogen.
[0010] Proton batteries have shown laboratory performance of up to one million charge-discharge cycles, allowing for decades of long-term operation. Proton batteries are made from inexpensive and abundant materials and are fully recyclable.
[0011] Proton batteries use the smallest energy carrier - protons, which, unlike lithium, have unprecedented properties: they can be charged at extremely high charging rates of up to 4000 C (<1 second), typically from 10 °C to 100 °C, meaning a charging time of 0.5 minutes to 6 minutes. Proton batteries are made from non-toxic and non-flammable materials, ensuring a high level of safety for the system. Proton batteries can operate at temperatures from -60 °C to 70 °C, under extreme conditions of high pressure and high humidity. In contrast, lithium-ion batteries cannot charge or discharge at low temperatures (especially below 0 °C). Some low-temperature lithium iron phosphate batteries can operate at temperatures from -20 °C to 60 °C.
[0012] The so-called "Grotthuss mechanism" (also known as proton hopping) enables protons to diffuse freely within the system, enabling rapid charging and discharging of the battery and a longer lifespan. This mechanism relies on the use of acidic electrolytes such as sulfuric acid (H2SO4), phosphoric acid (H3PO4), acetic acid (CH3COOH), hydrochloric acid (HCl), or citric acid (C6H8O7), etc. Optimal performance is obtained when using phosphoric acid.
[0013] The use of acidic electrolytes makes proton batteries safe and non-toxic. At the same time, the use of inexpensive manufacturing materials and the ultra-durable operation with over hundreds of thousands of charge-discharge cycles provide economic advantages. In particular, from the perspective of capital expenditure and the levelized cost of storage (LCoS), the cost of proton batteries is very low.
[0014] Advantageously, the manufacturing of proton batteries can be completed using traditional lithium-ion production lines, without the need for retooling or only with minimal retooling requirements.
[0015] Proton batteries have both characteristics similar to traditional lithium-ion batteries and some unique features of supercapacitors, and the disadvantages of proton batteries are not as significant as those of supercapacitors or batteries. Therefore, proton batteries lie between these two technologies.
[0016] Table 1 lists the general comparison:
[0017] Table 1
[0018]
[0019]
[0020] Proton battery technology continuously requires new chemistries and new efficiencies. SUMMARY OF THE INVENTION
[0021] An object of the present invention is to provide a cathode that can improve battery performance when used in a proton battery.
[0022] Another object of the present invention is to mitigate at least one drawback associated with the related art.
[0023] The object of the embodiments described herein is to overcome or mitigate at least one of the above drawbacks of the related art systems, or at least to provide a useful alternative to the related art systems.
[0024] In the broadest aspect, the present invention relates to a cathode and a method of manufacturing a cathode for a proton battery, the cathode comprising a Prussian blue analogue (PBA) coated on a current collector.
[0025] Prussian blue analogue (PBA)
[0026] Prussian blue (Fe7(CN) 18 Or more precisely Fe4[Fe(CN)6]3.xH2O) is a well-known chemical in the dye industry and is produced by the oxidation of ferrocyanide salts. Other Prussian blue compounds have one or more iron cations replaced by other metal cations and have a double perovskite structure with the chemical general formula A x Fe[Fe(CN)6] 1-y Υ y ·nH2O (A: alkali metal ion; Υ: vacancy; 0 ≤ x ≤ 2, 0 ≤ y < 1), where the (C≡N)-anion replaces the oxide ion in the perovskite structure.
[0027] The iron cation can be replaced by a variety of transition metals (including manganese, nickel, cobalt, zinc, copper, chromium, vanadium, and titanium) without disrupting the crystal structure. The resulting series of compounds has the same structure as A x Fe[Fe(CN)6] 1-y γ y·nH2O with similar chemical compositions and crystal structures are collectively referred to as "Prussian blue analogs" (PBA). Those skilled in the art should understand that depending on the metal substituents and their usual oxidation states, as well as whether the PBA is in the oxidized or reduced form, substitution can result in a variety of different molecular formulas. The prior art literature mentions various options. For example, some technicians in the art represent the general formula of PBA as A x P[R(CN)6] 1-y ·nH2O, where A is an intercalated ion such as potassium or sodium, P and R are transition metals (the R site is usually occupied by Fe), and Y is the number of [R(CN)6] vacancies. Other technicians in the art represent the general formula of PBA as A x P[R(CN)6]. In another representation, the general formula of PBA is represented as AM[M'(CN)6]·xH2O, where generally A = Li, Na or K, M, M' = transition metals, where generally M' = Fe, and sometimes M = M'. If M' = Fe, PBA is also often referred to as hexacyanoferrate, or if M' = other transition metals, PBA is also often referred to as hexacyanometallate.
[0028] Preferably, the PBA of the cathode of the present invention has the general formula M III 4[Fe II (CN)6]3, where M is a metal other than Fe. In another preferred embodiment, the PBA of the cathode of the present invention has the general formula Cu3[M(CN)6]2, where M = Fe, Co or Ir.
[0029] In a particularly preferred embodiment, the PBA is copper hexacyanoferrate Cu[Fe(CN)6]·XH2O, potassium copper hexacyanoferrate K2Cu[Fe(CN)6] or manganese hexacyanoferrate. In particular, copper hexacyanoferrate has shown excellent proton intercalation and storage capabilities. The PBA of the present invention can be prepared by any known technique. For example, copper hexacyanoferrate can be prepared by adding an excess of CuSO4·5H2O solution to K3Fe II (CN)6.
[0030] The term "PBA" as used herein is also intended to include pre-protonated PBA. Without wishing to be bound by theory, a large number of protons in pre-protonated PBA can improve the capacity and cycle stability of the electrode material by reducing capacity loss (especially in the early stage of charging or discharging).
[0031] However, many other PBAs are also suitable for the cathodes of the present invention, including PBAs containing aluminum, nickel, magnesium, lithium, sodium or other metals. However, it is important to note that water-soluble PBAs (such as alkali metal (sodium, potassium, lithium) ferrocyanides) cannot be used in proton batteries with aqueous electrolytes.
[0032] In a first aspect of the embodiments described herein, a cathode for a proton battery is provided, the cathode having a first layer and a second layer, the first layer consisting of PBA, battery-grade carbon nanoparticles, and a binder, and the second layer comprising a current collector.
[0033] Carbon nanoparticles
[0034] When used in reference to carbon, the term "battery-grade" is a term well-known in battery technology. Generally, battery-grade carbon has a very high purity (>99% carbon content), surface area, and electrical conductivity. Battery-grade carbon also has very low metal impurities, typically an iron content of less than five parts per million (ppm), and copper, nickel, cobalt, and zinc in the low ppm to ppb range, preferably less than 5 ppm. These impurities can have a negative impact on battery life, but in proton batteries operating at lower voltages compared to lithium batteries, this is not a major issue.
[0035] Generally, battery-grade carbon nanoparticles include carbon black (preferably acetylene black), graphene, or carbon nanotubes. The size of the nanoparticles is typically from 10 nanometers to 50 nanometers.
[0036] Binder
[0037] PBA and battery-grade carbon nanoparticles are typically combined with a non-water-soluble binder. The binder must bind the carbon nanoparticles and PBA together and help adhere them to the current collector. The binder also helps in dispersion to form a uniform slurry for the current collector and remains stable in the harsh battery environment where many reactions occur.
[0038] Binders suitable for the present invention include the fluoropolymer polyvinylidene fluoride (PVDF), which consists of a carbon backbone with multiple linked C-F bonds; silicate binders such as sodium silicate binder; and polycarbonate binders. The nature of the solvent that dissolves PVDF is also important for determining the properties of the first layer. PVDF is insoluble in most conventional organic solvents. Preferably, the binder of the present invention includes PVDF dissolved in a solvent such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), or dihydrolevoglucosenone (Cyrene TM , Cyrene is a trademark of Circa Group). Although relatively expensive, Cyrene TM solvent is particularly preferred due to its low toxicity and environmental impact.
[0039] It is noted that water-soluble binders are generally not suitable for the cathodes of the present invention using aqueous electrolytes. However, they may be suitable for non-aqueous electrolytes or solid-state batteries.
[0040] Current collector
[0041] The cathode current collector serves as the support for the first layer to collect the current generated by the cathode, thereby forming a larger output current to supply the external circuit. The presence of the current collector reduces the internal resistance of the battery and improves the current efficiency, cycle stability, and rate performance. The current collector of the present invention can be any suitable conductive electrode carrier, such as metal foil, metal foam, polymer film, and paper-coated metal substrate. Particularly preferred are metal foils, such as titanium foil, copper foil, aluminum foil; and carbon-based materials (including carbon paper containing carbon microfibers).
[0042] Battery Structure
[0043] In another aspect of the embodiments described herein, a proton battery is provided, comprising:
[0044] - a cathode having a first layer composed of PBA and battery-grade carbon material and a second layer including a current collector,
[0045] - a separator,
[0046] - an anode, and
[0047] - an electrolyte.
[0048] Preferably, the selection of electrode materials provides (i) high capacity, (ii) excellent rate performance, (iii) a wide operating voltage range, (iv) chemical stability, (v) non-toxic, green, and pollution-free, and (vi) substantially recyclable.
[0049] Anode
[0050] The anode can be any anode suitable for a proton battery, such as a carbon-supported platinum (Pt / C) anode or an "active" carbon anode previously used in traditional Prussian blue-based batteries. Tungsten trioxide (WO3) is an alternative anode material, as is carbon-coated titanium foil.
[0051] Conductive polymers and redox polymers are other potential anode options, including, for example, PEDOT and other thiophene derivatives.
[0052] Separator
[0053] The separator in the battery is typically a porous polymer membrane that serves as a barrier interface between the electrodes while allowing protons to be transported between the electrodes. Preferably, the separator material is stable, safe, and sustainable and does not degrade battery performance. The separator can be, for example, a conventional proton exchange membrane, such as Nafion TM (Nafion is a trademark of DuPont). Preferred Nafion TM membranes are N-112, N-115, N-117, NE-1135, or NE-1110. Other suitable separator materials include Pemion TM(Pemion is a trademark of Ionomr Innovations) or perfluorosulfonic acid (PFSA) membranes, such as those manufactured by Fumatech BWT GmbH, including Fumatech's FS-960-RF, FS-990-PK, F-10100, and F10150-PTFE.
[0054] In another aspect of the embodiments described herein, a method of manufacturing a cathode of a proton battery is provided, comprising the steps of:
[0055] - forming a slurry comprising PBA, battery-grade carbon nanoparticles, and a binder, and
[0056] - coating a layer of the slurry on a cathode current collector to form a cathode,
[0057] and optionally,
[0058] - compressing the coating,
[0059] - drying the coating,
[0060] - cutting the cathode into a desired shape.
[0061] In another aspect of the embodiments described herein, a method of manufacturing a proton battery is provided, comprising the step of combining the cathode of the present invention with a separator, an anode, and an electrolyte.
[0062] Embodiments may also be for preparing a solid-state proton battery by mixing a proton-conducting material (such as Nafion TM ) into the cathode material and the anode material and using a proton-conducting separator. It should be noted that such a device is not anhydrous but is still solid-state.
[0063] Other aspects and preferred forms disclosed in the specification and / or defined in the appended claims form part of the specification of the present invention.
[0064] In essence, the embodiments of the present invention stem from the recognition that the use of PBA (especially certain PBAs) can improve cathode and battery performance compared to equivalent Prussian blue-based cathodes and batteries.
[0065] Advantages provided by the present invention include:
[0066] · Economical to manufacture due to inexpensive and non-toxic materials;
[0067] · Ultra-fast charging rate and ultra-long life cycle,
[0068] · Maintenance comparable to traditional battery systems,
[0069] · Capital expenditure spread over hundreds of thousands of cycles (compared to 1000 cycles for lithium-ion batteries), and
[0070] · The overall efficiency is up to 97% (in contrast, the overall efficiency of lithium-ion batteries is lower than 93%).
[0071] Potential applications of the cathode and battery according to the present invention include:
[0072] · Automotive batteries,
[0073] · Batteries for vehicles that require continuous use with fast charging (such as forklifts and mine cars),
[0074] · Energy buffers for electric vehicle charging stations to reduce the burden on the power grid during charging,
[0075] · Stationary and grid-connected battery systems for renewable energy systems (for time-shifting of intermittent renewable energy by balancing loads),
[0076] · Dual battery packs, namely proton batteries and lithium-ion batteries,
[0077] · Home energy storage,
[0078] · Remote energy storage,
[0079] · Microgrid energy storage, and
[0080] · Support systems in mobile applications.
[0081] The further scope of applicability of the embodiments of the present invention will become apparent from the detailed description given hereinafter. However, it should be understood that the detailed description and specific examples, while indicating preferred embodiments of the invention, are given by way of illustration only, since various changes and modifications within the spirit and scope of the invention will become apparent to those skilled in the art from this detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Those skilled in the relevant art can better understand the preferred embodiments of the present application and the further disclosure, objects, advantages, and aspects of other embodiments by referring to the following description of the embodiments in conjunction with the drawings. The drawings are for illustrative purposes only and thus do not constitute a limitation to the disclosure herein, wherein:
[0083] · FIG. 1 is a flowchart showing the cathode manufacturing steps according to an embodiment of the present invention. Figure 1A The steps of generating a solid mixture are shown. Figure 1B The steps of preparing a slurry and applying the slurry onto a current collector are shown.
[0084] · FIG. 2 shows a schematic diagram of a proton battery suitable for the cathode of the present invention in the discharge mode ( Figure 1A ) and the charging mode ( Figure 1B ). Detailed implementation mode
[0085] The cathode of the present invention can be based on PBA (such as copper ferrocyanide or manganese ferrocyanide), and is usually mixed with nanoparticle acetylene black, graphene, carbon nanotubes or other battery-grade carbon materials in the presence of a binder.
[0086] These three components are mixed to form a slurry, which is then wet-applied to the cathode carrier. The cathode can then be dried and cut into a suitable shape. The cathode can then be encapsulated together with the anode, separator and electrolyte to form a proton battery.
[0087] Conventional water-insoluble battery binders are suitable, such as polyvinylidene fluoride (PVDF), which is widely used as a lithium-ion battery binder dissolved in N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), Cyrene TM or other suitable solvents.
[0088] This is described in more detail in FIG. 1, which is a flow chart showing the cathode manufacturing steps according to a preferred embodiment of the present invention. Figure 2A The step of generating a solid mixture is shown. Figure 2A The step of preparing a slurry and applying the slurry on a current collector is shown.
[0089] Although FIG. 1 shows the use of copper ferrocyanide as PBA, it is readily understood that a variety of other PBAs can be synthesized and used in the described method, including PBAs containing aluminum, nickel, magnesium, lithium, sodium or other metals. However, it is important to note that water-soluble PBAs (such as alkali metal (sodium, potassium, lithium) ferrocyanides) cannot be used in proton batteries with aqueous electrolytes.
[0090] Preparation of solid mixture
[0091] In a preferred embodiment of the present invention as Figure 1A shown, a 0.1M solution can be prepared by dissolving potassium ferrocyanide in deionized water (10); and a 0.2M copper sulfate (II) solution is formed by dissolving copper sulfate (II) in deionized water (11). Then, the copper sulfate (II) solution (13) can be added dropwise to the potassium ferrocyanide solution (12) over 8 hours with stirring (13) to form PBA nanoparticles.
[0092] The PBA nanoparticles can be filtered out of the solution using a centrifuge and then washed thoroughly with deionized water (more than three times) (14). As an alternative to a centrifuge, filter paper or other similar filtration techniques can be used. The filtrate can be dried in a vacuum oven for 8 hours until dry. Alternatively, drying can be carried out on a hot plate or other suitable drying device.
[0093] Then, use a mortar and pestle to crush the dry PBA into powder (15), or use any convenient means to crush the dry PBA into powder. Then mix the powdered PBA with battery-grade carbon material (16).
[0094] Figure 1B The step of mixing battery-grade PVDF (or other water-insoluble battery binders) with N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), Cyrene TM or some other suitable solvent is shown (17). Then mix it with the powdered PBA (18) to form the cathode slurry.
[0095] The cathode slurry can be coated (19) onto a conductive carrier made of titanium (20) using a doctor blade or other suitable device. As an alternative to the doctor blade, other wet coating techniques can be used. Additionally, as an alternative to titanium, the carrier (current collector) can include a carbon pad or some other conductive carrier.
[0096] The cathode prepared as such can be dried (21), for example, in a vacuum oven, on a hot plate, or in other drying devices. In another embodiment of the method, compression can be applied before drying to compress the cathode slurry. Then, the cathode can be cut and assembled into the battery.
[0097] Except for limited drying and compression, Figure 2A and Figure 2B the method shown can be carried out at room temperature and pressure without the need for an inert atmosphere.
[0098] The selection of a suitable conductive cathode carrier or current collector depends on its conductivity, and also on its ability to withstand hundreds of thousands of charge and discharge cycles, extended battery life, and the ability to remain chemically inert under acidic conditions.
[0099] The separator can be a conventional proton exchange membrane (such as Nafion TM ), which provides excellent performance due to its proton conduction properties. In one embodiment, a glass fiber separator is used instead of the proton exchange membrane, which can reduce costs compared to the Nafion membrane; however, this combination exhibits lower battery performance. Other membranes are also used, including Pemion TM or perfluorosulfonic acid (PFSA) membranes. The present invention can work with a variety of other proton-conducting membranes suitable for working under acidic electrolyte conditions. A cation exchange membrane can also be used in the proton battery of the present invention.
[0100] A typical proton battery using the cathode according to the present invention is shown in Figure 2. The proton battery 1 includes a cathode according to the present invention, which includes a first catalyst layer 2 and a current collector layer 3. The anode having a catalyst layer 4 is generally made of a material (such as tungsten trioxide or Pt / C) deposited on the current collector layer 5. A separator 6 (such as Nafion TM ) and an acidic aqueous electrolyte 7 are provided between the two electrodes. The arrows indicate the proton flow through the separator when the proton battery 1 is charged and discharged.
[0101] The present invention is further described with reference to the following non-limiting examples.
[0102] Example 1 - Preparation of the Cathode
[0103] A cathode slurry was prepared by mixing cupric ferrocyanide with carbon black nanoparticles and PVDF binder in a mass ratio of 6:3:1. The slurry was coated on a 0.1 mm thick titanium foil current collector. The active mass of the cathode was 23 g·m -2 . For example, a higher active mass loading can be obtained by using a slurry with a mass ratio of cupric hexacyanoferrate, carbon black, and PVDF of 12:3:5. The relative capacity of the battery was 53 mA·g -1 .
[0104] The cathode slurry was wet-coated onto the cathode current collector using a doctor blade to obtain a layer with uniform thickness. Then the cathode coating was compressed, followed by drying and cutting the cathode into the desired shape.
[0105] Then the cathode was encapsulated together with the anode, separator, and electrolyte to form a proton battery.
[0106] Two types of proton battery module batteries have been fabricated according to the above steps - (i) small test button cells, and (ii) pouch cells. Cylindrical proton battery module batteries, battery packs, and battery systems are considered to be within the scope of the present invention.
[0107] Example 2 - Synthesis of Copper PBA
[0108] PBA suitable for the cathode of the present invention was synthesized by dropping a 0.2 M CuSO4·5H2O solution into an equal volume of 0.1 M K3Fe II (CN)6 while continuously stirring the solution. The dropping was carried out manually using a pipette, but it can also be carried out using an automatic dropper or other suitable techniques known in the art.
[0109] Excess copper sulfate pentahydrate was added to K3[Fe II (CN)6]3 to ensure that all of the K3[Fe II (CN)6]3 was converted.
[0110] The reaction proceeds for more than 8 hours until copper hexacyanoferrate crystals are formed and the reaction is complete. The crystalline precipitate is washed three times with deionized water and then dried in a vacuum oven at a high temperature for more than 8 hours until completely dry.
[0111] Water and ethanol can also be used for washing. As an alternative, centrifugation and ultrasonication or any other technique known in the art can be used to separate the precipitate and the solution. In most cases, a simple paper filter can be used to collect the copper hexacyanoferrate precipitate.
[0112] Anode
[0113] Platinum on carbon (Pt / C) anodes or "activated" carbon anodes are suitable for proton battery cells. The counter electrode used to test the performance of the cathodes produced according to the present invention comprises a 0.1 mm thick titanium foil coated with activated carbon, carbon black and a PTFE or PVDF binder in a mass ratio of 7:2:1. The mass loading of the counter electrode varies between 200 g·m -2 and 400 g·m -2 -2.
[0114] For a practical proton battery setup, tungsten trioxide (WO3) anodes are used to obtain a proton battery full cell with an average voltage exceeding 1 V. Tungsten trioxide (WO3) is an anode material that exhibits a slightly higher cell voltage. To obtain better conductivity, slightly oxygen-deficient (i.e., WO 2.96 or the like) is an option.
[0115] Another anode setup relies on a platinum on carbon (Pt / C) electrode made by coating a current collector with 20% Pt / C and PVDF in a mass ratio of 9:1.
[0116] Conductive polymers and redox polymers are other potential non-noble metal anode options. In particular, polyaniline groups may be suitable because their redox reactions involve proton exchange under acidic conditions (which is also the most stable under acidic conditions). Poly(3,4-ethylenedioxythiophene) (PEDOT) and other thiophene derivatives are noted for their stability and have been used to replace Pt / C electrodes in various types of solar cells.
[0117] Conductive polymers also offer the possibility of adjusting the anode potential. The same is true for redox polymers (which are inherently non-conductive but contain redox-active groups in the repeating units, which allows charge hopping to occur). Redox polymers have been studied for potential fast-charging battery applications. Blends of conductive polymers and redox polymers have been fabricated to obtain better conductivity and maintain the unique redox behavior of the redox polymers (see International Patent Publication WO 2012 / 121417).
[0118] Although the present invention has been described in connection with its specific embodiments, it is to be understood that it can be further modified. This application is intended to cover any variations, uses, or modifications of the present invention, which generally follow the principles of the present invention and include departures from the present disclosure that are known or conventional in the practice of the art to which the present invention pertains and departures that can be applied to the basic features set forth above.
[0119] Without departing from the spirit of the basic features of the present invention, the present invention can be embodied in various forms. Therefore, it is to be understood that unless otherwise specified, the above embodiments do not limit the present invention, but should be construed broadly within the spirit and scope defined by the appended claims. The described embodiments are to be considered in all respects only illustrative and not restrictive.
[0120] Various modifications and equivalent arrangements are intended to be included within the spirit and scope of the present invention and the appended claims. Accordingly, the specific embodiments are to be understood as illustrative of many ways in which the principles of the present invention can be practiced. In the following claims, the means-plus-function clauses are intended to cover structures that perform the defined functions, including not only structural equivalents but also equivalent structures.
[0121] When a Markush group or other grouping is used herein, all individual elements of the group and all combinations and possible subcombinations of the group elements are intended to be individually included in the present disclosure. Each combination of components described or exemplified herein can be used to practice the present invention unless otherwise stated.
[0122] Whenever a range is given in the specification, for example, a temperature range, a time range, or a composition or concentration range, all intermediate ranges and subranges, as well as all individual values included in the given range, are intended to be included in the present disclosure. It should be understood that any subrange or range or individual value included in the specification can be excluded from the claims herein.
[0123] As used herein, "comprising" is synonymous with "including", "containing", or "characterized by", and is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. As used herein, "consisting of" excludes any element, step, or ingredient not specified in the claim element. As used herein, "consisting essentially of" does not exclude materials or steps that do not materially affect the basic and novel characteristics of the claim. The broad term "comprising" is intended to cover the narrower "consisting essentially of" as well as the narrower "consisting of". Thus, in any recitation herein of the phrase "comprising one or more claim elements" (e.g., "comprising A"), the phrase is intended to cover the narrower recitations, e.g., "consisting essentially of A" and "consisting of A". Thus, the broader word "comprising" is intended to provide specific support for "consisting essentially of" or "consisting of" in each instance of its use herein. The invention as described illustratively herein can be practiced without any one or more elements, one or more limitations not specifically disclosed herein.
[0124] Those skilled in the art will appreciate that materials and methods not specifically exemplified can be used in the practice of the invention without undue experimentation. All known functional equivalents of any such materials and methods are intended to be included in the invention. The terms and expressions employed are used as descriptive terms and not of limitation, and in using such terms and expressions there is no intention to exclude any equivalents of the features shown and described or portions thereof, and it should be recognized that various modifications are possible within the scope of the invention as claimed. Thus, it should be understood that although the invention has been specifically disclosed by way of example, preferred embodiments, and alternative features, those skilled in the art can make modifications and variations to the concepts disclosed herein, and such modifications and variations are considered to be within the scope of the invention as defined by the appended claims.
[0125] Each reference cited herein is incorporated herein by reference in its entirety. These references can provide sources of materials, alternative materials, method details, and other uses of the invention.
Claims
1. A cathode for a proton battery, the cathode comprising a Prussian blue analogue (PBA) coated on a current collector.
2. The cathode for a proton battery according to claim 1, wherein the PBA is formed from Prussian blue in which Fe cations are replaced by transition metal cations.
3. The cathode for a proton battery according to claim 1, wherein the PBA is formed from Prussian blue having one or more iron cations replaced by transition metal cations and having a double perovskite structure.
4. The cathode for a proton battery according to claim 1, wherein the PBA has the general formula M III 4[Fe II (CN)6]3, where M is a metal other than Fe, or the PBA has the general formula Cu3[M(CN)6]2, where M = Fe, Co or Ir.
5. The cathode for a proton battery according to claim 1, wherein the PBA is copper hexacyanoferrate or manganese hexacyanoferrate 6. The cathode for a proton battery according to claim 1, wherein the cathode has a first layer and a second layer, the first layer being composed of PBA and battery-grade carbon nanoparticles, the second layer comprising a current collector, and the first layer being coated on the second layer.
7. The cathode for a proton battery according to claim 1, wherein the PBA is combined with battery-grade carbon nanoparticles and a water-insoluble binder.
8. The cathode for a proton battery according to claim 1, wherein the ratio of PBA:carbon nanoparticles:binder is from 6:3:1 to 12:3:
5.
9. The cathode for a proton battery according to claim 7, wherein the battery-grade carbon is in the form of nanoparticles having a size of 10 nm to 50 nm, and the battery-grade carbon comprises greater than 99% carbon, and respectively less than 5 ppm of iron, copper, nickel, cobalt, and zinc.
10. The cathode for a proton battery according to claim 7, wherein the water-insoluble binder comprises polyvinylidene fluoride dissolved in a solvent selected from N-methyl-2-pyrrolidone, N,N-dimethylformamide, or dihydrolevoglucosenone.
11. The cathode for a proton battery according to claim 7, wherein the current collector is selected from metal foils, metal foams, polymer films, and paper-coated metal substrates.
12. A proton battery, comprising: - a cathode according to any one of the preceding claims, - a separator, - an anode, and - an electrolyte.
13. The proton battery according to claim 11, wherein the anode is selected from platinum on carbon, activated carbon, tungsten trioxide, carbon-coated titanium foil, conductive polymers, and redox polymers.
14. A method of manufacturing the cathode for a proton battery according to claim 1, the method comprising the steps of: - forming a slurry comprising PBA, battery-grade carbon nanoparticles, and a binder, and - coating a slurry layer on a cathode current collector to form the cathode.
15. The method of manufacturing a cathode according to claim 13, the method further comprising the steps of: - compressing the coating, - drying the coating, and - cutting the cathode into a desired shape.
16. A proton battery, comprising a cathode according to any one of claims 1 to 11.
Citation Information
Patent Citations
Conducting polymer / redox polymer blends via in-situ oxidative polymerization - preparation methods and application as an electro-active polymeric materials
WO2012121417A1